The modelling of productivity level and the comparability of sport evaluation depending on the athlete age - Portnaia, I A; Demakov, V I; Rerke, V I; Larionova, E Y; Golodkov, Y E (Advances in gerontology = Uspekhi gerontologii, 2021)
Throughout the life, a person's working capacity is variable. It is influenced by a wide range of factors, both external and internal, which are difficult to take into account in various studies. An approximation of the density function of the given distribution, based on the assumption of the random nature of the physical condition, depending on a number of different reasons, among competitors and the hypothesis of the asymmetric distribution of athletes' achievements, shown at different ages, is formed. Optimum parameters of a log-normal distribution describing the working capacity of a person according to his or her age are determined by using the least squares method. This is a comparative analysis of the received model and the previously known methods, which were created by Litvinov and Spiridonov. The study has showed the validity of the method for determining age coefficients and the possibility of its practical application.Throughout the life, a person's working capacity is variable. It is influenced by a wide range of factors, both external and internal, which are difficult to take into account in various studies. An approximation of the density function of the given distribution, based on the assumption of the random nature of the physical condition, depending on a number of different reasons, among competitors and the hypothesis of the asymmetric distribution of athletes' achievements, shown at different ages, is formed. Optimum parameters of a log-normal distribution describing the working capacity of a person according to his or her age are determined by using the least squares method. This is a comparative analysis of the received model and the previously known methods, which were created by Litvinov and Spiridonov. The study has showed the validity of the method for determining age coefficients and the possibility of its practical application.